An Educational CT Scanner Prototype of a 3rd Generation CT Scanner - Sim Ting Lim; Yit Hein Yow; Way Soong Lim; Chee Siong Lim; Li Wah Thong (International Journal of Integrated Engineering, 2025)
This project aims to develop an affordable educational prototype of a3rd generation CT scanner. The proposed prototype uses non-radiativelight sources and combines 3D printing, electronics components, andfiltered backprojection (FBP) algorithm to generate the cross-sectionimage of a transparent phantom. Key components include an LED light,an Arduino Nano controller, and a camera. The prototype can captureup to 200 images per scan cycle and successfully reconstruct theinternal structures of the phantom. However, there were somelimitations, including issues with the dataset, light source power, andtime efficiency. Results showed that the prototype could create a 3Dmodel of the lemon phantom, though it faced challenges due to the lightsource and data limitations. Educational workshops were conductedwith 38 students and the prototype was well received by the studentsas shown by the questionnaire results. Future improvements will focuson increasing dataset resolution, using more powerful light sources likelaser diodes, and upgrading the camera system for better image qualityand faster processing.